Empirical investigation of the theory of production funktion, with the data of alloy production in Ukraine - Matsuki, Y.; Bidyuk, P.; Kozyrev, V. (Видавництво Львівської політехніки, 2013)
У формі математичної твірної функції вивчено таке поняття, як “мікроекономічна теорія” з фактичними даними для заводу в Дніпропетровській області України, який виготовляє сплави з декількох вхідних матеріалів. Лінійний вигляд твірної функції описує модель, яка складається зі змінних, які презентують матеріали разом з їх ваговими коефіцієнтами. Для перетворення цієї моделі було використано метод множників Лагранжа з метою знайти умови максимального виходу продукції за заданих обмежень на витрати. Отримано умови реальних математичних відношень між цінами і обсягами сировини, в які входять невідомі коефіцієнти. Для отримання значень вагових коефіцієнтів проведено статистичний аналіз фактичних даних. Результат показує статистичну значущість моделі. Тому можна зробити висновок, що обрана лінійна функція може бути твірною функцією. In this research, a mathematical form of production function is investigated, which is a concept of microeconomics theory, with the actual data from the factory in Dnepropetrovsk Region of Ukraine, which produces the alloys from several input materials. A linear form of the production function was selected as the model, which consists of the variables that represent input materials together with their weighting factors, then the Lagrangean multiplier technique was used to transform this model in order to find the conditions for maximizing the output of the production, under a given cost constraint. The obtained conditions present the mathematical relations between the prices and the quantities of the input materials, which include unknown weighting factors. In order to get the values of the weighting factors, statistical analysis is made with the actual data. The result shows statistical significance of the model, therefore it is concluded that the selected linear function can be the production function.
Keywords: твірна функція; множник Лагранжа; статистичний аналіз; лінійна функція; production function; Lagrangean multiplier technique; statistical analysis; linear function